Aplikasi China Tourism Berbasis Android - Budiono, Fenny Valentine; Handojo, Andreas; Purbowo, Anita Nathania (Jurnal Infra, 2015)
China is one of the overseas tourist destination for the people in the world, including the Indonesian people. Before travelling, required an applications that can help tourists prepare for their trip to China. The preparations are studying the culture, attractions, and daily conversation. In addition, because the Chinese characters is unique, learn Chinese need to be studied first. In this thesis, developed Android application that provides information related to Chinese tourism.Android application in this thesis can display information about the culture in China, provides list of daily conversation, review attractions in China, and Chinese-Indonesian translator with the input of the picture. Attraction location will be shown on the map, and the application can help the user to get towards the tourist attraction. Features translator can recognize Chinese characters from the image, and translate it into Indonesian. This application is made with Eclipse IDE in the Java programming language, using a library Tesseract OCR Engine as optical character recognition library.The test results showed that the application can operate on multiple Android devices. Applications can run cultural, conversation, attractions, and translator feature. Performance Tesseract OCR Engine on translators features indicate that tolerance tilt angle of the input image approximately equal to 15 degrees.